Respuesta :

Answer:

a)

[tex]x=-1\\x=-\frac{3}{4}[/tex]

b)

[tex]x=\frac{11}{6}[/tex]

Step-by-step explanation:

[tex]Formula: x=\frac{-b\frac{+}{}\sqrt{b^2-4ac} }{2a}[/tex]

[tex]a)-4x^2+7x-3=0[/tex]

a= -4

b= 7

c= -3

[tex]x=\frac{-(7)\frac{+}{}\sqrt{(7)^2-4(-4)(-3)} }{2(-4)}[/tex]

[tex]x=\frac{-7\frac{+}{}\sqrt{49-48} }{-8}[/tex]

[tex]x=\frac{-7\frac{+}{}\sqrt{1} }{-8}[/tex]

[tex]x=\frac{7\frac{+}{}1 }{-8}[/tex]

------------------------------

[tex]x=\frac{7+1 }{-8}=\frac{8}{-8}=-1[/tex]

or

[tex]x=\frac{7-1 }{-8}=\frac{6}{-8}=-\frac{3}{4}[/tex]

------------------------------

[tex]b)36x^2-132x+121=0[/tex]

a= 36

b= -132

c= 121

[tex]x=\frac{-b\frac{+}{}\sqrt{b^2-4ac} }{2a}[/tex]

[tex]x=\frac{-(-132)\frac{+}{}\sqrt{(-132)^2-4(36)(121)} }{2(36)}[/tex]

[tex]x=\frac{132\frac{+}{}\sqrt{17424-17424} }{72}[/tex]

[tex]x=\frac{132\frac{+}{}\sqrt{0} }{72}[/tex]

[tex]x=\frac{132\frac{+}{}0 }{72}[/tex]

------------------------------------------------

[tex]x=\frac{132}{72}[/tex]

[tex]x=\frac{132/6}{72/6}=\frac{22}{12}=\frac{11}{6}[/tex]